A Systematic Review of the 2016 National Academy of Engineering Exemplary Ethics Programs: Revisions to a Coding Framework. - Hess, Justin L.; Kerr, Alison J.; Lin, Athena; Chung, Andrew (Science & Engineering Ethics, 2023)
Engineering ethics is a required aspect of accredited ABET programs, but there is widespread variation in how ethics is taught, to what ends, and how those ends are assessed. This variation makes it challenging to identify practices for teaching ethics to engineers aligned with extant practices in the field. In this study, we revise a recent coding framework by reviewing exemplary engineering ethics programs recognized by the National Academy of Engineering in 2016, or what we refer to as "exemplars." We pursue two primary objectives: (1) To apply and revise a prior coding framework to codify ethics learning objectives, instructional strategies, and assessment strategies in engineering education; and (2) To use the revised coding framework to identify trends in learning objectives, instructional strategies, and assessment strategies of NAE exemplars. We employ systemic review procedures to update the coding framework using 24 of 25 exemplars as a data source. The updated framework includes four primary categories associated with learning objectives, instructional strategies, assessment data collection strategies, and assessment design characteristics. Results indicate that ethical sensitivity or awareness was present in every exemplar as a learning objective, often alongside ethical reasoning-based learning objectives and the formation of professional skills. Exemplars employed numerous instructional strategies in tandem, as we coded eight out of 18 instructional strategies among at least half of the exemplars. Assignments/homework and summative reflections were the most oft-used sources of assessment data. Due to our challenges in coding assessment approaches, we offer practical suggestions for assessing engineering ethics instruction which are based on many of our coding discussions. We hope that this coding framework, the results classifying exemplary features of the NAE programs, and our practical suggestions can guide future instructors as they design, classify, assess, and report their approaches to engineering ethics education.